2000
DOI: 10.1143/jjap.39.3683
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Fibers in Liquid by Ultrasonic Standing Waves

Abstract: The orientation of fibers in a liquid irradiated with ultrasound is studied to realize the noncontact directional control of reinforcing fibers in the molten matrix of a composite material. The equations of translational and rotational motions of a fiber in a standing wave field are derived. The numerical solutions show the movement of the fibers at various initial positions and their stable positions and directions. Experiments are performed using polystyrene fibers of various lengths suspended in an aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 11 publications
4
46
0
Order By: Relevance
“…Cold model experiments 74) revealed that rod-like fibers shorter than one-fourth of the wavelength are constrained at the pressure node and are oriented in the direction perpendicular to that of wave propagation. On the other hand, fibers ranging from one-fourth to one-half of the wavelength were oriented either parallel to the direction of wave propagation at the pressure loop or perpendicular to that at the pressure node depending on their initial positions and directions.…”
Section: Ultrasonically Assisted Designing Of Compositementioning
confidence: 99%
“…Cold model experiments 74) revealed that rod-like fibers shorter than one-fourth of the wavelength are constrained at the pressure node and are oriented in the direction perpendicular to that of wave propagation. On the other hand, fibers ranging from one-fourth to one-half of the wavelength were oriented either parallel to the direction of wave propagation at the pressure loop or perpendicular to that at the pressure node depending on their initial positions and directions.…”
Section: Ultrasonically Assisted Designing Of Compositementioning
confidence: 99%
“…This time-averaged torque is the underlying principle of the noncontact rotational manipulation, which has been applied to control the orientation of fibers in a fiber-reinforced composite 1 and in a paper pulp. 2 King studied the case of a circular disk in a plane progressive or stationary sound field.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber will always align with the direction of the potential well. The torque on a fiber can be evaluated by modeling the fiber as a chain of spheres as shown by Yamahira et al 23 For a cavity surrounded by hard boundary walls the different possible pressure modes with their corresponding potential force fields can be calculated. A single mode excited inside the cavity can be expressed as (m,n), where the first variable stands for the number of nodes of the pressure wave in the x-direction and the second variable stands for the number of nodes in the y-direction.…”
Section: Theorymentioning
confidence: 99%
“…23-25. Yamahira et al 23 studied the behavior of polystyrene fibers in a one-dimensional standing wave. The application is the directional control of reinforcing fibers in composite materials.…”
Section: Introductionmentioning
confidence: 99%